2019
DOI: 10.1039/c8an01591k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and SINS analysis of the cell wall integrity response ofAspergillus nidulansto the absence of galactofuranose

Abstract: With lethal opportunistic fungal infections on the rise, it is imperative to explore new methods to examine virulence mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The cell walls of fungi were also studied. Bakir et al 77 identified the nanoscale structure and chemical components of the cell wall of the gene deletion strains by s-SNOM. Li et al 61 used PFIR with a resolution of 6 nm to reveal the chemical composition and distribution of yeast cell wall particles.…”
Section: Test Results and Analysismentioning
confidence: 99%
“…The cell walls of fungi were also studied. Bakir et al 77 identified the nanoscale structure and chemical components of the cell wall of the gene deletion strains by s-SNOM. Li et al 61 used PFIR with a resolution of 6 nm to reveal the chemical composition and distribution of yeast cell wall particles.…”
Section: Test Results and Analysismentioning
confidence: 99%
“…Joined by other modalities, s-SNOM has been participating in fungi and bacteria research as a superresolution chemical resolving tool to reveal nanoscale chemical heterogeneities. Bakir et al have used s-SNOM with synchrotron radiation to obtain mid-IR spectra from specific points on single fungi cells of Aspergillus nidulans [83]. In addition to architecture alterations of two gene deletion strains compared to the wild type A. nidulans, compositional changes were also discovered by a series of near-field spectra.…”
Section: S-snom In the Characterization Of Virus Fungi And Bacteriamentioning
confidence: 99%
“…A relatively new correlative method uses synchrotron-based infrared nanospectroscopy (SINS) to illuminate an AFM tip for the dual purpose of nanoscale imaging while using near-field infrared spectroscopy to report on local chemical groups just nanometers below the tip (Bakir et al, 2019). SINS of the opportunistic pathogen Aspergillus nidulans and its mutants lacking the sugar galactofuranose, involved in pathogenicity and cell wall function, showed changes in cell wall biochemistry and surface roughness, best attributed to the cell wall integrity pathway (Bakir et al, 2019).…”
Section: Tracking Cell Wall Changes With Correlative Afm-microspectroscopymentioning
confidence: 99%
“…A relatively new correlative method uses synchrotron-based infrared nanospectroscopy (SINS) to illuminate an AFM tip for the dual purpose of nanoscale imaging while using near-field infrared spectroscopy to report on local chemical groups just nanometers below the tip (Bakir et al, 2019). SINS of the opportunistic pathogen Aspergillus nidulans and its mutants lacking the sugar galactofuranose, involved in pathogenicity and cell wall function, showed changes in cell wall biochemistry and surface roughness, best attributed to the cell wall integrity pathway (Bakir et al, 2019). Kochan et al (2018) used a similar approach to monitor dynamic changes in the cell wall of six bacterial species, including pathogenic S. aureus and E. coli, during cell division, showing changes to complex carbohydrate and phosphodiester groups, including peptidoglycans and teichoic acid, and enabling discrimination of Gram-positive and Gram-negative cell wall components.…”
Section: Tracking Cell Wall Changes With Correlative Afm-microspectroscopymentioning
confidence: 99%